Physical and mechanical properties of Thermoplastic Natural Rubber (TPNR) nanocomposites - Hassan, Noor Azlina; Hassan, Norita; Ahmad, Sahrim; Rasid, Rozaidi; Anuar, Hazleen; Bonnia, Noor Najmi; Surip, Siti Norasmah (Trans Tech Publications, Switzerland, 2012)
Thermoplastic natural rubber (TPNR) nanocomposites were prepared by melt blending method with the optimum mixing parameters (140oC, 100 rpm, 12 min) using internal mixer (Haake 600 P). The aim of this work is to study the effects of organo-montmorillonite (OMMT) on the physical and mechanical properties of TPNR with and without coupling agent (maleic anhydride grafted polyethylene, MA-PE). Significant improvement in tensile strength and modulus of TPNR nanocomposites were obtained with the presence of MA-PE.